Pluralitas Makhluk dan Keesaan Khâliq - Tahir, Gustia (Jurnal Adabiyah, 2016)
This article aimed to describe the Islamic perspective on the concept of the plurality of creatures and the unity of Khaliq. The problem was about the notion of plurality, plurality of creatures and Khaliq oneness, and wisdom behind the plurality of creatures and Khaliq oneness. This study found that plurality can create dynamism in the life of human being, but the potential difference in it -which, if not addressed proportionally will bring the conflict to bring the victims, the losses even collapse. Plurality beings and the unity of the Creator to bring awareness that the existence of a pluralistic life is derived from the One God. Plurality created as God’s way of giving choice to the creature to determine the path that has consequences for their choice.